2009
DOI: 10.1128/jvi.02231-08
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vif mRNA Splicing by Human Immunodeficiency Virus Type 1 Requires 5′ Splice Site D2 and an Exonic Splicing Enhancer To Counteract Cellular Restriction Factor APOBEC3G

Abstract: The human immunodeficiency virus type 1 (HIV-1) accessory protein Vif is encoded by an incompletely spliced mRNA resulting from splicing of the major splice donor in the HIV-1 genome, 5 splice site (5ss) D1, to the first splice acceptor, 3ss A1. We have shown previously that splicing of HIV-1 vif mRNA is tightly regulated by suboptimal 5ss D2, which is 50 nucleotides downstream of 3ss A1; a GGGG silencer motif proximal to 5ss D2; and an SRp75-dependent exonic splicing enhancer (ESEVif). In agreement with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 33 publications
6
23
0
Order By: Relevance
“…Recently it was shown that splicing to exon 2A, another incompletely spliced HIV-1 exon that encodes the vif gene, appears to be positively regulated by SRp75 through the interaction of SRp75 with an enhancer in this region (46,47). We show that SRp75 can induce production of vpr mRNA by inhibiting the 5Ј-splice site of exon 3.…”
Section: Discussionmentioning
confidence: 81%
“…Recently it was shown that splicing to exon 2A, another incompletely spliced HIV-1 exon that encodes the vif gene, appears to be positively regulated by SRp75 through the interaction of SRp75 with an enhancer in this region (46,47). We show that SRp75 can induce production of vpr mRNA by inhibiting the 5Ј-splice site of exon 3.…”
Section: Discussionmentioning
confidence: 81%
“…Increased splicing at 3Јss A1, on the other hand, results in an increased level of Vif, a 10-fold inhibition of virus production, and also, surprisingly, a defect of Gag processing (24,26). We showed in those studies that the strength of U1 snRNP binding at 5Јss D2 is important for regulation of splicing at 3Јss A1 but that splicing at 5Јss D2 is not required for this regulatory effect (25). Similarly, mutations of 5Јss D3 that change it to a consensus 5Јss result in increased splicing at 3Јss A2 (9).…”
mentioning
confidence: 90%
“…1A) (13,23,24). Mutations of 5Јss D2 that increase its binding affinity for U1 snRNP result in increased splicing at 3Јss A1 and increased vif mRNA, whereas mutations which lower the affinity to U1 snRNP result in decreased splicing at 3Јss A1 and reduced vif mRNA (13,25). Decreased splicing at 3Јss A1 reduces the level of Vif and inhibits HIV-1 replication in cells that are expressing elevated levels of the restriction factor APOBEC3G (25).…”
mentioning
confidence: 99%
“…Thus, the 5=ss D2 has to be rendered splicing incompetent, even though binding of U1 snRNP to this 5=ss is a prerequisite for efficient recognition of the upstream 3=ss A1 (22,23). In general, 5=ss splice donor repression may be a common requirement for the generation of all spliced but intron-containing HIV-1 mRNAs, e.g., the env mRNAs (24).…”
mentioning
confidence: 99%
“…Thus, the 5=ss D2 has to be rendered splicing incompetent, even though binding of U1 snRNP to this 5=ss is a prerequisite for efficient recognition of the upstream 3=ss A1 (22,23). In general, 5=ss splice donor repression…”
mentioning
confidence: 99%